2022
DOI: 10.1177/00208728211073648
|View full text |Cite
|
Sign up to set email alerts
|

Supervision of supervisory practice: From idea to practice

Abstract: Little is known about how social work supervisors can be equipped and supported. A qualitative evaluation of a supervision of supervisory practice (SOSp) training programme with nine supervisors with 2 years of experience was done. Benefits for the supervisors were the application of knowledge and skills that improved the supervisory practice, and the opportunity to receive feedback. However, lack of time was a major obstacle for quality supervision. Supervisees reported experiencing a more collaborative super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…This social work practice demonstrated that supervision is fundamental for and in professional development and professional quality (Choi, 2017;Newcomb, 2022;Tsui, 2005), given it emphasizes the management of emotions, especially in complex situations such as (illness, death, suffering) as well as work overload (more hours of work, more tasks related to public health rules, etc.) (Beddoe et al, 2022;Wong et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This social work practice demonstrated that supervision is fundamental for and in professional development and professional quality (Choi, 2017;Newcomb, 2022;Tsui, 2005), given it emphasizes the management of emotions, especially in complex situations such as (illness, death, suffering) as well as work overload (more hours of work, more tasks related to public health rules, etc.) (Beddoe et al, 2022;Wong et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The supervisor is frequently a Social Work professional with a lot of experience in pedagogical supervision and support. It is one of the main requirements for the development of supervisory processes, i.e., supervisors in addition to having case management skills, they must have pedagogical training and supervision support (Wong et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Social work supervision also involves administrative, educative, and supportive functions, each working in tandem to ensure that social workers are supported in their work, delivering professional, quality services, and that clients are being protected from harm [36][37][38]. Research on social work supervision has shown that supervision not only improves the quality of services that social workers provide to clients [39][40][41][42][43][44], but that supervision also reduces work stress and increases job satisfaction amongst supervised social workers [45][46][47][48]. Mor Barak et al performed a meta-analysis of 27 social work supervision studies.…”
Section: Concept and Function Of Social Work Supervisionmentioning
confidence: 99%